COMPARISON OF TRADITIONAL AND INNOVATIVE TECHNOLOGIES IN TOMATO DRYING - Qurbonova Oftoboyim Husniddinovna; Qobilova Nargiza Ixtiyorovna (Web of Journals Publishing, 2025)
This article presents a scientific comparison of traditional and innovative technologies used in tomato drying. The effects of solar and convective drying methods, as well as vacuum, infrared, microwave, and freeze-drying technologies, on the quality, energy efficiency, and nutritional value of the final product are analyzed.
Keywords: Tomato; drying technology; traditional methods; innovative technologies; comparison.